Crack assessment in spiral-welded pipelines repaired by composite patch: A SMART and failure assessment diagram approach - Ardeshir Savari (Journal of Pipeline Science and Engineering)
This study presents a methodology for assessing cracks in spiral-welded pipelines (SWPs) repaired with composite sleeves, utilizing the Separating Morphing and Adaptive Remeshing Technique (SMART) for crack growth modeling and a failure assessment diagram (FAD) approach. Stress analysis identifies critical regions for crack initiation, and Ansys™ Mechanical software is used for automated remeshing to study crack growth. Various scenarios are considered, including stationary cracks and those that grow under static or cyclic loading. A parametric analysis examines the impact of factors such as crack dimensions, internal pressure, sleeve mechanical properties, and repair thickness on both non-repaired and repaired models. Safety factors are derived using the FAD curve, accounting for both conservative and non-conservative fracture criteria. The study finds that composite repairs are more effective for deep, long cracks than for shallow, short ones. Although the evaluation of stress intensity factors (SIFs) and stresses might suggest safety, FAD assessments indicate potential failure risks, necessitating urgent repairs. The extracted safety factors demonstrate the effectiveness of composite patches in enhancing the reliability of SWPs, regardless of employing a conservative or non-conservative approach. This methodology provides valuable insights into the assessment and repair of SWPs with composite sleeves.